The promise of attending to literary context for contextual biblical hermeneutics in Africa - D.W. Ellington (Acta Theologica)
For important reasons, African contextual hermeneutics raises the main question: “What does the Scripture mean to us and our community?”. This article asserts that the reader-centred approach tends to allow the voice of the community to ring louder than the voice of Scripture. Repercussions can include a limited role of Jesus Christ and a heightened role of material prosperity in some African expressions of Christian faith. The article argues that contextual hermeneutics needs to make room for the inductive analysis of biblical texts, especially their literary contexts. The heart of a combined inductive and contextual approach is inviting readers to a dialogue between text and context, asking questions that help them use literary context to observe the main aims, themes, and lines of thought of passages of Scripture, and that foster a deep identification between biblical texts and the readers’ context.